BUDGET CONTROL FOREIGN DEVELOPMENT OF EAST KALIMANTAN PROVINCE - Heriyanto dan Damianus Rudiansyah (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2018)
Criteria that are important to determine the ability of agencies in managing households in the agency can be seen from its financial position. The financial position can be seen from the Budget Realization Report (LRA) that determines the amount of agency expenditure to finance all activities in each budget year.  The purpose of this research is to know the Control of Budget of Forestry Service of East Kalimantan Province in 2016. Based on the results of analysis and discussion on research, then the conclusion Based on the results of analysis and discussion on research, the conclusions obtained are as follows:1.       Viewed Ratio of Growth Spending Budget Control of East Kalimantan Provincial Forestry Office 2016 Efficiency due to Expenditure in 2016 has increased.2.       Viewed Operating Expenditure Ratio Against Total Expenditure Budget Control of East Kalimantan Provincial Forestry Office 2016 Efficiency due to Actual Expenditure of Operations in 2016 decreased.3.       Capital Expenditure Ratio to Total Expenditure Budget Control of East Kalimantan Provincial Forestry Office 2016 Efficiency due to Actual Expenditure of Operations in 2016 decreased.4.       Direct Ratio of Direct Expenditure and Indirect Expenditure Budget Control of East Kalimantan Provincial Forestry Office 2016 Unstable due to Expenditure of Operations Expenditure in 2016 has increased.5.       Viewed Ratio of Efficiency of Expenditure Budget Control of East Kalimantan Provincial Forestry Office 2016 Enough Efficiency due to Realization of Expenditure in 2016 less than Budget. Based on the above conclusions of the East Kalimantan Provincial Forestry Service's Budget Control. It is reviewed from the Growth Ratio of Expenditure, the Ratio of Expenditure on Total Expenditure, the Ratio of Capital Expenditure to Total Expenditure, the Ratio of Direct Expenditure and Indirect Expenditure, the Efficient Easier Expense Ratio of 2016, Accepted